The biological role of hemolymph lectins in Episesarma tetragonum - VR Devi; MR Basil-Rose; MD Pallaty (Invertebrate Survival Journal, 2013)
The hemolymph of the mangrove crab, E. tetragonum contains lectins specific for NeuGcα 2, 3 Gal β1-4 GluNAc β1 linkage and O-acetyl sialic acids. The role of sialic acid specific lectins on natural immunity of the crab is studied by using several kinds of mammalian erythrocytes as pathogen model. Injection of erythrocytes showing differential agglutinability with the lectins, induced augmentation of hemagglutinating activity suggesting an increase in the circulating lectins. A significant correlation was observed between in vivo clearances of exogenous erythrocytes with the extent of erythrocyte agglutination by the lectins. Another correlation was observed between the susceptibility of erythrocytes to lectin dependent hemocyte mediated hemolysis and the extent of lectin mediated erythrocyte agglutination. This study documents that opsonization of foreign pathogen by the native lectins is an important step in hemocyte recognition, hemolysis and clearance of the pathogen.